Antarctic coastal microalgal primary production and photosynthesis - McMinn, A; Ashworth, C; Bhagooli, R; Martin, A; Salleh, S; Ralph, P; Ryan, K (Marine Biology, 2012)
Primary production in coastal Antarctica is primarily contributed from three sources: sea ice algae, phytoplankton, and microphytobenthos. Compared to other eastern Antarctic sites, the sea ice microalgal biomass at Casey Station, in spring 2005 was relatively low, 3.841.67 to 21.613.3mg chl- a m −2 but productive, 103163mgCm −2 day −1 . The photosynthetic parameters, F v / F m and rETR max , imply a community well-acclimated to the light climate of the benthic, water column, and sea ice habitats. Phytoplankton biomass was greatest in late spring (11.10.920μg chl- a l −1 ), which probably reflects input from the overlying sea ice. Lower biomass and depressed F v / F m values later in the season were probably due to nutrient limitation. Benthic microalgal biomass was consistently between 200 and 400mg chl- a m −2 and production increased through into late summer (204mgCm −2 day −1 ). After the sea ice broke out, the marine environment supported a small phytoplankton biomass and a large benthic microalgal biomass. Compared with previous studies, F v / F m values were relatively low but there was no evidence of photoinhibition. When sea ice was present, primary production of benthic microalgae was either very low or there was a net draw down of oxygen. The benthic microalgal community made a larger contribution to total primary production than the phytoplankton or sea ice algae at water depth less than approximately 5m.